(untitled) (ELang | An English Language Education Journal, 2020)
This research entitled “Improving Students’ Vocabulary Mastery by Using Audio Visual Media” for the first grade students of MTs. Darul Hikam Al-Islami Banjaran in academic of 2020/2021. The aims of this research are to find out the effectiveness of audiovisual media in improving students’ vocabulary mastery at the first grade of MTs. Darul Hikam Al-Islami Banjaran and to know whether or not the students like being taught the vocabulary using audiovisual media. The population of this research is first grade students of MTs. Darul Hikam Al-Islami Banjaran. The sample of this research is 30 students of VIIB. This research applied pre-experimental design which consist of one independent variable in teaching English vocabulary using animation video. The instruments of this research are pre-test, post-test and questionnaire. The pre-test is used to know the students’ vocabulary mastery before the treatments. The post-test is used to know the influence of audiovisual media toward the first grade students. And the Questionnaire in this research is given to analyze the students’ response. The result of the questionnaire is to answer the research question and support the result statement. Then, in this research, the data is analyzed by using t-test formula. The result of this research is showed that there is significant improvement of students’ vocabulary after using audio visual media. This statement can be proven by the t-test = 3.665 does exceed the table critical value of t-table = 2.045, at p = .05 with df = 29 (3.665 > 2.045). It means that the students’ vocabulary from pre-test to post-test is classified successful. And it also means that audiovisual media is effective for teaching vocabulary to the first grade students of Junior High School. Then, from the result of questionnaire above, the researcher found out the students’ response toward audiovisual media in teaching vocabulary is good or in other words, the students give the positive response. It means, the students like being taught the vocabulary using audiovisual media. Therefore, audiovisual media can improve the students’ vocabulary mastery.